Syntactic features of headlines and notes on baseball in electronic versions of Mexican newspapers - Quintero Ramírez, Sara (Lenguas Modernas, 2016)
In this paper, we examine the most relevant syntactic features that characterize a corpus consisting of fifty baseball headlines and their relationship with the rest of the article. In this study, we wish to compare and contrast syntactic characteristics between the baseball headlines and the articles. First, we identified the syntactic features in the headlines, more specifically the type of construction and its configuration. After that, we examined the articles identifying anaphors and verbal tenses and moods. The most important feature we found is that the main referent, which is presented in the headline in the form of brief noun phrases, is reconsidered very regularly throughout the article through a diversity of noun phrases of different lengths. Moreover, although verbal moods and tenses of the headlines do not coincide with those of the baseball article, there is perfect cohesion and coherence in the journalistic text as a whole.